Frenemies : When Ideological Enemies Ally - Haas, Mark L. (Book collections on Project MUSE., 2021)
"The author develops an argument that explains when international ideological enemies are likely to ally to balance shared material threats. He tests its predictions in three cases: British and French alliance policies toward the Soviet Union in the 1930s, China's alliance policies toward the United States in the 1970s, and Turkey's alliance policies with Israel in the 2000s"--